Analisis Pengaruh Kualitas Pelayanan, Persepsi Kemudahan dan Kepuasan Pelanggan Terhadap Keputusan Pembelian Pada Jasa Brilink Raisa di Kecamatan Rumbia - Indra Kurniawan; Selamet Fuadi; Herry Novrianda (Universitas Muhammadiyah Metro, 2026)
The purpose of this study is to find out whether the quality of service affects the decision to buy back. To find out if the perception of convenience affects the repurchase decision. and to find out if customer satisfaction affects the purchase decision. The sample of this study is BRIlink Raisa customers totaling 65 respondents. Data collection uses questionnaires and literature studies. Data analysis uses instrument prerequisite testing , namely validity test and reliability test . The analysis test uses the normality test and the linearity test . The hypothesis test uses multiple linear regression analysis , partial test (Test T), Joint Test (Test F) and Coefficient of Determination (R2) using a program (SPSS). The results of the study show that 1).Service quality has an influence and significance on purchasing decisions 2).The perception of convenience has no effect and is not significant to the purchase decision. 3).Customer satisfaction has an effect and is significant on purchasing decisions